Գանձակյան հայատառ պարսկերեն ձեռագիր Ավետարանը վիճաբանական թարգմանությունների համատեքստում - Կիրակոսյան, Հասմիկ (Մատենադարան)
In Safavid Iran one of the means of Islamization was propaganda which included anti-Christian literature and confessional debates. Polemic treatises against Christianity, commentaries on religious matters (also by apostates and converts to Islam) were written and translation projects in the genre of dalāʻil al-nubuwwah (proofs of prophecies) were carried out. In response to the Islamic propaganda, the Armenian Church was sponsoring the creation of relevant literature and the translation of the Gospels, in order to promote the knowledge of the Christian doctrine and confront the Muslim preachers in Muslim-Christian debates. The Armeno-Persian handwritten Gospel (M 3044) was copied in 1780 for supporting the religious identity of the Armenian community in Safavid Iran and resisting the Islamic propaganda. В Сефевидском Иране одним из инструментов исламизации была пропагандистская деятельность, в рамках которой создавалась антихристианская литература и проводились межрелигиозные диспуты с целью доказать превосходство ислама. Писались авторские трактаты, в которых опровергались богословские догматы христианства, либо создавались переводы священных книг в жанре далаʻил ал-нубува (доказательства пророчеств), а также распространялись сочинения вероотступников. В условиях исламской пропаганды армянская церковь покровительствовала созданию соответствующей литературы, в том числе перевода Евангелия. Рукопись № 3044 Матенадарана (1780 г.), арменографический персидский перевод с армянского Четвероевангелия, написана, чтобы помочь армянам сохранить религиозную идентичность под игом Сефевидского Ирана и противостоять исламской пропаганде.
Keywords: Ավետարան; Թարգմանություններ